Pengaruh Terapi Murottal terhadap Halusinasi Pendengaran pada Pasien Skizofrenia di Kota Samarinda - Halipah Nurajijah; Dwi Rahmah Fitriani; Mukhripah Damaiyanti (KEWINUS: Jurnal Keperawatan dan Kesehatan, 2025)
Mental disorders are conditions in which an individual experiences disturbances in brain function, behavior, and emotions, leading to significant changes. Schizophrenia is one of the most prevalent mental disorders and is characterized by symptoms such as hallucinations, particularly auditory hallucinations. Murottal therapy is known to provide a relaxation effect through changes in brainwave activity. This study aimed to determine the effect of murottal therapy on patients with auditory hallucinations in Samarinda City. This research employed a quasi-experimental design with a pretest-posttest with control group. The sample consisted of 32 respondents divided into 16 participants in the experimental group and 16 in the control group, recruited from Sempaja Public Health Center, Juanda Public Health Center, and the Joint Adulam Ministry Foundation. The instrument used in data collection was the Auditory Hallucinations Rating Scale (AHRS). The experimental group received murottal therapy using Surah Ar-Rahman verses 1–78 for 15 minutes through an MP3 audio file. The results showed that the Independent t-test indicated a significant difference between the experimental and control groups, with a p-value of 0.000 (<0.05), indicating a reduction in auditory hallucination intensity following the murottal therapy. The study concludes that murottal therapy has a significant effect in reducing the intensity of auditory hallucinations among patients with schizophrenia and can be recommended as a supportive non-pharmacological intervention in the management of hallucinations.